UI/UX дизайн сайту для курсу QA Engineer - Панчук, Арсен Валерійович; Panchuk, Arsen Valeriyovych (Ірпінь, 2024)
Розробка прототипу ефективного UI/UX дизайну сайту для курсу QA Engineer, який допоможе навчальному закладу залучити більше слухачів на курс та зробити його більш популярним; розробка макету UI/UX дизайн сайту для курсу QA Engineer, враховуючи вимоги сучасного веб-дизайну

Development of a prototype of an effective UI/UX site design for the QA Engineer course, which will help the educational institution attract more students to the course and make it more popular; development of a layout UI/UX site design for the QA Engineer course, taking into account the requirements of modern web design
UI/UX website design for the QA Engineer course
Keywords: UI дизайн; UX дизайн; веб-інтерфейс; принципи дизайну; дизайн сайту для курсу QA Engineer; UI design; UX design; web interface; design principles; site design for the QA Engineer course